ANALISIS MEDAN MAKNA ‘SENI BELA DIRI KHAS JEPANG’ DALAM HURUF KANJI BU (武) - Irwan Irwan; Mulyadi Mulyadi (Universitas Diponegoro, 2017)
(Title: Meaning Field Analysis Of 'Japan's Martial Arts' In Kanji’s Letter Of Bu (武) )This research analyze the kind of words exist in the semantic field of the lexem of kanji BU (武) in Japanese, and how the lexical relation and the semantic feature were formed on each word that exist in one of semantic field. The lexem of kanji BU (武) is literally translated as martial arts, which is general meaning and also has derivatives meaning (hyponim), it creates the semantic field. The type of the research is qualitative research using inter lingual match method. The basic technique method used in this research is the technique of determining element (PUP technique) which applying equal compare connect technique (HBS) and the difference compare connect technique (HBB). The data taken from the book